Cadmium acute exposure induces metabolic and transcriptomic perturbations in human mature adipocytes. (30th March 2022) - Gasser, Marie; Lenglet, Sébastien; Bararpour, Nasim; Sajic, Tatjana; Wiskott, Kim; Augsburger, Marc; Fracasso, Tony; Gilardi, Federica; Thomas, Aurélien
Abstract: Obesity is considered as a major public health concern with strong economic and social burdens. Exposure to pollutants such as heavy metals can contribute to the development of obesity and its associated metabolic disorders, including type 2 diabetes and cardiovascular diseases. Adipose tissue is an endocrine and paracrine organ that plays a key role in the development of these diseases and is one of the main target of heavy metal accumulation. In this study, we determined by inductively coupled plasma mass spectrometry cadmium concentrations in human subcutaneous and visceral adipose tissues, ranging between 2.5 nM and 2.5 µM. We found a positive correlation between cadmium levels and age, sex and smoking status and a negative correlation between cadmium and body mass index. Based on cadmium adipose tissue concentrations found in humans, we investigated the effects of cadmium exposure, at concentrations between 1 nM and 10 µM, on adipose-derived human mesenchymal stem cells differentiated into mature adipocytes in vitro. Transcriptomic analysis highlighted that such exposure altered the expression of genes involved in trace element homeostasis and heavy metal detoxification, such as Solute Carrier Family transporters and metallothioneins. This effect correlated with zinc level alteration in cells and cellular media. Interestingly, dysregulation of zinc homeostasis and transporters has been particularly associated with the development of obesity and type 2 diabetes. Moreover, we found that cadmium exposure induces the pro-inflammatory state of the adipocytes by enhancing the expression of genes such as IL-6, IL-1B and CCL2, cytokines also induced in obesity. Finally, cadmium modulates various adipocyte functions such as the insulin response signaling pathway and lipid homeostasis. Collectively, our data identified some of the cellular mechanisms by which cadmium alters adipocyte functions, thus highlighting new facets of its potential contribution to the progression of metabolic disorders. Highlights: Cadmium (Cd) induces strong metabolic and transcriptomic changes in human adipocytes. Cd leads to the dysregulation of zinc homeostasis in human adipocytes. Dysregulation of adipocyte functions by Cd affects fat storage and insulin signaling. Cd has a pro-inflammatory effect in human adipocytes.